Potential 3D filament of Janeng (Dioscorea hispida Dennst) starch: Preparation and characterization - Chairul Amni; Marwan; Sri Aprilia; Eti Indarti (South African Journal of Chemical Engineering, 2024)
The preparation and characterization of filaments from janeng have been studied. The janeng filament (PCl-JS) process starts with the preparation and gelatinization of janeng starch, and then the resulting starch gelatinization, which is usually called thermoplastically processable starch (TPS) is carried out by filament processing by mixing PCl-g-GMA and JS at a temperature of 170 °C and 80 rpm for 15 min. The prepared filaments were analyzed. SEM studies show that the fracture surface of PCl-JS0 filaments provides a uniform fiber dispersion, in contrast to the morphology showing large and interconnected starch domains as the starch concentration increases from 1% to 9%. The intensity of hydrogen bonds observed in the spectrum via FTIR increased in band as the concentration of JS increased. XRD analysis observed that the crystallinity and crystal size of filaments without starch were higher than those of other PCl filaments that had undergone modification with starch. Mechanical analysis showed that starch did not have a negative effect on the tensile strength of the filaments, indicating good compatibility between JS and the PCl matrix. When the additional concentration of JS increased to 9%, the strength of PCl-JS filaments increased to 37 MPa, which was caused by the higher crystallinity induced by starch. The glass temperature of the filament sample was observed using DSC, which showed that PCl without JS occurred at 48.2 °C and shifted (+2 °C) towards 49.4 °C when JS was added. For all DSC curves, the exothermic peak was observed around 56–59 °C. The melt flow behavior of PCl-JS filaments decrease with increasing starch content.